Application of High Tech Architecture Theme in the Design of Science and Technology Demonstration Centers in Banda Aceh - Giyanda Rahmaningtyas (Universitas Syiah Kuala, 2019)
Banda Aceh Science Center is an educational recreation facilities that are designed to develop the motivation of citizen, especially students to understanding the principles of science and visualize science in visual form. The material indeed presented are variety of model science and can be played by visitors. High tech architecture approach implemented as the concept of applying science and technology of the building according to building functions. Characteristic of high tech architecture applied to building exterior and interior, so that visitors can find out the buildings that are designed have the same form and function related to innovative technological developments. The use of transparent glass elements is more dominant used in buildings as well as exposed structures and utilities out of the building. Keywords: sci-tech, high tech architecture, exposed structures and utilities